PETA KENDALI MULTIVARIAT np - irma irma; Dewi Anggraini; Fuad Muhajirin Farid (RAGAM: Journal of Statistics & Its Application, 2022)
In general, a production process requires the control of multiple quality characteristics (variables). Multivariate control charts can be used to control many quality attributes and identify the root cause of an out-of-control condition or signal. It was used in the production of Hexagon Bolt M16x75mm. However, research regarding the theory of multivariate control charts remains limited. The np multivariate control chart is obtained by combining the processes of parameter estimate, control limit determination, and out-of-control signal detection.  Keywords:  Control Charts, Multivariate np, Out of Conrol Signal.